2019
DOI: 10.1016/j.autrev.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity, safety and tolerability of anti-pneumococcal vaccination in systemic lupus erythematosus patients: An evidence-informed and PRISMA compliant systematic review and meta-analysis

Abstract: This is a repository copy of Immunogenicity, safety and tolerability of anti-pneumococcal vaccination in systemic lupus erythematosus patients: An evidence-informed and PRISMA compliant systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…A total of 32 systematic reviews focused on non-COVID-19 vaccines ( Table 3 ). Several vaccines were studied, including inactivated hepatitis A vaccine [ 32 ], recombinant hepatitis B vaccine [ 33 , 34 , 35 , 36 , 37 , 38 ], recombinant human papillomavirus vaccines [ 39 , 40 ], inactivated influenza vaccine [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], live-attenuated measles vaccine (given post hematopoietic stem-cell transplantation [ 52 ] and in children living with human immunodeficiency virus [ 53 ]), pneumococcal conjugate and polysaccharide vaccines [ 46 , 49 , 54 , 55 , 56 ], live-attenuated and recombinant subunit zoster vaccines [ 57 , 58 ], live-attenuated yellow fever vaccine [ 59 ], and others [ 60 , 61 , 62 , 63 ]. Immunocompromised states studied included use of B-cell-depleting anti-CD20 therapy, chronic kidney failure, human immunodeficiency virus infection, immune-mediated inflammatory diseases, liver cirrhosis, malignancy, post-splenectomy status, and solid organ transplant recipients.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 32 systematic reviews focused on non-COVID-19 vaccines ( Table 3 ). Several vaccines were studied, including inactivated hepatitis A vaccine [ 32 ], recombinant hepatitis B vaccine [ 33 , 34 , 35 , 36 , 37 , 38 ], recombinant human papillomavirus vaccines [ 39 , 40 ], inactivated influenza vaccine [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], live-attenuated measles vaccine (given post hematopoietic stem-cell transplantation [ 52 ] and in children living with human immunodeficiency virus [ 53 ]), pneumococcal conjugate and polysaccharide vaccines [ 46 , 49 , 54 , 55 , 56 ], live-attenuated and recombinant subunit zoster vaccines [ 57 , 58 ], live-attenuated yellow fever vaccine [ 59 ], and others [ 60 , 61 , 62 , 63 ]. Immunocompromised states studied included use of B-cell-depleting anti-CD20 therapy, chronic kidney failure, human immunodeficiency virus infection, immune-mediated inflammatory diseases, liver cirrhosis, malignancy, post-splenectomy status, and solid organ transplant recipients.…”
Section: Resultsmentioning
confidence: 99%
“…49 Immunogenicity post vaccination with inactivated vaccines appears to depend on the dose and duration of prednisolone therapy. 50 A study of the influenza vaccine in patients with SLE showed a trend of reduced immunogenicity in patients taking prednisolone >10 mg daily (mean number of immune responses 1.14 vs 1.65), although this was not a significant difference. 51 Dosage related reduction in antibody response has also been observed with the pneumococcal vaccine.…”
Section: Prednisolonementioning
confidence: 98%
“…No serious adverse events with pneumococcal vaccine were reported in a systematic review of studies in patients with systemic lupus erythematosus ( 119 ) or in 4 observational studies in patients with IBD ( 15 , 115–117 ).…”
Section: Inactivated Vaccines In Patients With Inflammatory Bowel Diseasementioning
confidence: 99%